Osseointegrating and phase-oriented micro-arc-oxidized titanium dioxide bone implants - Hsien-Te Chen; Hsin-I Lin; Chi-Jen Chung; Chih-Hsin Tang; Ju-Liang He (Journal of Applied Biomaterials & Functional Materials, 2021)
Here, we present a bone implant system of phase-oriented titanium dioxide (TiO 2 ) fabricated by the micro-arc oxidation method (MAO) on β-Ti to facilitate improved osseointegration. This (101) rutile-phase-dominant MAO TiO 2 (R-TiO 2 ) is biocompatible due to its high surface roughness, bone-mimetic structure, and preferential crystalline orientation. Furthermore, (101) R-TiO 2 possesses active and abundant hydroxyl groups that play a significant role in enhancing hydroxyapatite formation and cell adhesion and promote cell activity leading to osseointegration. The implants had been elicited their favorable cellular behavior in vitro in the previous publications; in addition, they exhibit excellent shear strength and promote bone–implant contact, osteogenesis, and tissue formation in vivo. Hence, it can be concluded that this MAO R-TiO 2 bone implant system provides a favorable active surface for efficient osseointegration and is suitable for clinical applications.